Inclusive visual arts educator profile in Higher Education (Educational Knowledge, 2023)
This research aims to characterize the profile of an inclusive visual arts educator within the visual arts program. Employing an ethnographic method, the study involves interviews and direct observation of visual arts educators at the Rafael Ángel Gallegos Ortiz University Center of the University of Los Andes, Venezuela. The focus is on inclusive practices in classrooms with students on the autism spectrum. Analysis of interviews and observations unveils characteristics of the inclusive visual arts educator in higher education. The study draws on international, national, and regional treaties influencing educational policies and practices.
Keywords: Inclusion in visual arts; educator profile; visual arts; inclusive education; educational policies; autism